External orientation and domestic market promotion - Heinrich Dehn (Intereconomics, 1988)
The increasing differentiation among developing countries, revealed by many indicators, also suggests that they have need of differing trade and development strategies. The following article reviews the across-the-board advice offered by agencies including the World Bank to “the” developing countries—“outward-orientation”, integration into the world economy, trade liberalisation-in the light of persistent shortages of foreign exchange and the limited capacity for structural adjustment, diversification and raising export levels in low-income primary commodity, exporting countries.
Keywords: 330; International Division of Labour